CRIMINAL LIABILITY FOR PERFORMERS OF ILLEGAL ONLINE INVESTMENTS USING PONZI SCHEMES - Dana Satwika, Sarita; Made Swardhana, Gde (Penerbit Lafadz Jaya, 2023)
Technology and information are advancing at a rapidly increasing pace in the current era of globalization. Unfortunately, many of the benefits of technological progress are being abused as they spread. The fraudulent crime mode is just one of the many new types of crime that are constantly popping up. Ponzi schemes have become more common in online illegal investment scams in recent years. This study aims to understand better the regulation of illegal online investment crimes with the Ponzi scheme in Indonesia and the criminal liability for illegal online investment actors with the Ponzi scheme in Indonesia. This writing uses normative legal research. In this article, illegal online investment with Ponzi schemes has started operating in Indonesia. This writing discusses the unregulated form of illegal online investment with Ponzi schemes in Indonesia. Illegal online investment with this Ponzi scheme is related to Article 378 of the Criminal Code and the Information and Electronic Transaction Law. In the case of illegal online investments with Ponzi schemes, the perpetrators will promise the victims large profits quickly. The absence of clear regulations regarding forms of illegal online investment fraud with the Ponzi scheme in Indonesia impacts the unclear criminal responsibility for perpetrators who invest illegally online with the Ponzi scheme in Indonesia.